Kajian Komposisi Formulasi Dan Dosis Nutrien Untuk Budidaya Tanaman Selada (Lactuca Sativa l.) dengan Sistem Hidroponik Substrat - Fitri Rahmaningsih (Corolla: Jurnal Sains Pertanian, 2015)
Lettuce (Lactuca sativa L.) is a crop of vegetables highlands and lowlands. Production of lettuce can be improved by means of hydroponics. According to the Linga (1984), a major factor in the successful conduct of hydroponics is the exact mix of mineral salt solution is given in accordance with the purposes of the plant. The purpose of this study was to determine the effect of formulations and doses of nutrien on the growth and yield of lettuce (Lactuca sativa L.) grown in the lowlands in the shade of a plastic roof. The method used is Complete Random Design (RAL) are arranged in a factorial with two factors and three replications. The results showed that out of a number of growth parameters and production there is interaction between treatment with a dose of formulations nutrien.